A RAPID ISOCRATIC HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC-UV) METHOD FOR THE QUANTIFICATION OF RITONAVIR IN HUMAN PLASMA - A. K., Hemanth Kumar; V., Sudha; A., Leelavathi; Ramachandran, Geetha (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: An accurate, simple, and rapid HPLC-UV based method for the quantitative determination of ritonavir (RTV) in human plasma is developed. Methods: The method involved deproteinization of the sample with 0.125N NaOH and methyl tertiary butyl ether and evaporated to dryness. The residue was reconstituted with mobile phase (20 mM Sodium Acetate and Acetonitrile–55:45 v/v). The analysis was done using C8 column (250 x 4.6 mm ID) and detection at a wavelength of 212 nm Results: The method range was linear over the range 0.5–10.0 µg/ml as derived using calibration curve method. Mean intra-and inter-day variations over the ranges of the standard curves were less than 10 % and mean extraction recoveries from human plasma ranged from 96 to 110 %. Conclusion: A rapid and accurate method for quantitation of RTV in plasma was validated. The assay spans the concentration range of clinical interest. The easy sample preparation and small sample size makes this assay highly suitable for pharmacokinetic studies of RTV in HIV-infected patients with TB. Keywords: Ritonavir, Pharmacokinetics, HPLC, Plasma extraction, HIV